1970
DOI: 10.1149/1.2407730
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Aluminum with Sodium Hydroxide Solution as a Source of Hydrogen

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 1 publication
1
55
0
Order By: Relevance
“…However, the generation of hydrogen gas from Al/water system is slow due to the thin layer of aluminum oxide on the surface of Al. The generation of hydrogen can be achieved by using highly corrosive basic solution such as sodium hydroxide (pH>13) [2]. Additives such as aluminum hydroxide [3], sodium stannate in sodium hydroxide solution [4], [5], hot water [6], CaO [7] were reported to be effective for enhanced generation of hydrogen, where serious corrosive conditions can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…However, the generation of hydrogen gas from Al/water system is slow due to the thin layer of aluminum oxide on the surface of Al. The generation of hydrogen can be achieved by using highly corrosive basic solution such as sodium hydroxide (pH>13) [2]. Additives such as aluminum hydroxide [3], sodium stannate in sodium hydroxide solution [4], [5], hot water [6], CaO [7] were reported to be effective for enhanced generation of hydrogen, where serious corrosive conditions can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Where, mb = wet mass, mk = dry mass, mu = vapor mass, ρ = density, φ = porosity, and Vt = measured volume. Herein, the value of mu is relative for each material and mu cannot be used to determine the porosity since the materials are synthetic materials.…”
Section: Density and Porosity Testsmentioning
confidence: 99%
“…The reaction between aluminium and water, catalyzed by NaOH, has been elaborated in the previous studies [5][6], as shown in the following equation: From Eq. (1), the oxidation of aluminium produces hydrogen [7][8][9] and sodium aluminium hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…∆S = 26.2 J/K und ∆G = −284 KJ [12]) is a suitable reaction for aluminosilicate sodalite synthesis. Besides providing of the whole heat energy for the synthesis process even the aluminate source for sodalite formation is produced under these aqueous alkaline conditions too, according to the reaction [13]:…”
Section: Bhmentioning
confidence: 99%